2018
DOI: 10.1002/csr.1709
|View full text |Cite
|
Sign up to set email alerts
|

Do corporate social responsibility ratings affect credit default swap spreads?

Abstract: We examine the impact of a corporate social responsibility (CSR) rating announcement on the credit default swap (CDS) spreads of European firms. Our results indicate that a CSR rating upgrade leads to an immediate and significant decrease in CDS spreads of rated firms. In contrast, CSR rating downgrades do not have a significant immediate impact on the CDS market. Additionally, better CSR ratings, in terms of both the overall score and the scores for the three main CSR pillars (economic, environmental, and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…ESG investments may also be perceived as agency costs because managers can improve their own reputation by investing in ESG at the expense of shareholders (Barnea & Rubin, 2010). If investors adopt this view, they may give greater relevance to the increase in firms' fixed costs associated with stronger ESG in which case investors may regard such firms as riskier (Drago, Carnevale, & Gallo, 2019).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…ESG investments may also be perceived as agency costs because managers can improve their own reputation by investing in ESG at the expense of shareholders (Barnea & Rubin, 2010). If investors adopt this view, they may give greater relevance to the increase in firms' fixed costs associated with stronger ESG in which case investors may regard such firms as riskier (Drago, Carnevale, & Gallo, 2019).…”
Section: Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Other studies have also analysed the relation of CSR performance with either the cost of companies' financing (Attig et al, 2011), with how bonds perform (Sharfman & Fernando, ), with either the credit default swap (Drago, Carnevale, & Gallo, ) or the stock market (Miralles‐Quiros, Miralles‐Quiros, & Guia, ). This last study revealed that, in general, European stock market investors value the CSR information published by listed companies for decision making, but this study found differences between markets.…”
Section: Background and Research Hyphotesismentioning
confidence: 99%
“…Rating refers to the evaluation of the quality, performance, and outcomes of entities, individuals, and organizations (Drago et al, ; Elsbach & Kramer, ). It is often regarded as a “social test” that distinguishes the good from the bad (Rao, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Lee et al () also found that firms that are highly rated are more likely to initiate online communication with stakeholders than those that are poorly rated. Drago et al () found that although the upgrade of CSP rating leads to an immediate and significant decrease in credit default swap spreads of rated firms, the downgrade does not have a significant immediate impact on the credit default swap market. However, to our knowledge, beyond the above several studies, few other studies have examined firm response to being rated.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation